The Contribution of E-Commerce to the Lowering of Operational Costs - Raipuria, Dr. Anil (Innovative Research Thoughts, 2021)
E-commerce has completely altered the manner in which organisations function, opening up brand new doors to prospects for expansion as well as cost reduction. E-commerce has the potential to reduce operating expenses, which in turn enables firms to become more productive and competitive. This is one of the most important advantages of e-commerce. the influence that e-commerce has had on inventory management, shipping, and marketing specifically, as well as how it has contributed to the reduction of overall operating expenses. Because internet sales enable more precise forecasting and the capability to swiftly refill stock as required, the requirement for firms to have big inventories on hand has been significantly decreased as a result of the rise of e-commerce. Because of this, we have been able to save a considerable amount of money on the costs of managing, transporting, and storing our goods. Through the use of e-commerce, firms have the ability to conduct their operations with a reduced number of physical storefronts since they can serve clients from all over the globe through their online storefronts. E-commerce has had a significant influence on a number of different fields, including logistics. The capability to trace shipments and optimise delivery routes has resulted in the fulfilment of orders being completed more quickly and effectively, which in turn has led to a reduction in the expenses incurred by enterprises. Additionally, many e-commerce platforms now offer lower delivery rates, which further cuts down on overall operating expenses. E-commerce, as a last point of discussion, has fundamentally altered the marketing strategies used by firms. When compared to more conventional marketing channels, online advertising's ability to run focused campaigns that communicate with certain demographics of consumers results in a greater return on investment. The use of social media platforms, in example, provides companies with the opportunity to advertise their products or services to a larger audience at a cheaper cost than would be required by conventional advertising techniques.